STUDENTS’ PERCEPTION TOWARDS THE IMPLEMENTATION OF ONLINE FORMATIVE ASSESSMENT IN ENGLISH LEARNING - Komang Lisna Kristiyanti; Made Hery Santosa; Ni Putu Astiti Pratiwi (SAGA: Journal of English Language Teaching and Applied Linguistics, 2021)
The Indonesian government policy due to the emergence of the COVID-19 pandemic requires all students and teachers to carry out the learning process online. Starting from various learning strategies to the assessment process must be carried out by applying an online system. In line with this policy, this study was conducted with the aim of investigating the implementation of one type of assessment, namely formative assessment in online learning situations. This study focuses on students’ perceptions of the implementation of formative assessment in English learning. By using a mixed-method research design, data collection was carried out through survey and interview methods. The samples of this study were 215 students of a Junior High School in Bali, Indonesia and involved 8 students from the entire sample as participants in the interview. The survey results showed that students had a positive perception of the implementation of online formative assessment. This is also supported by information obtained in the interview process, in which students feel that this type of online formative assessment is comfortable to carry out, especially because of the use of simple and easy tools. In addition, students also feel that there are things that make online formative assessment less effective, such as the unavailability of feedback which also causes students to be less interested in this type of assessment. Through this study, it is hoped that it can provide various information for students and teachers for the purpose of improving the quality of the implementation of formative assessment in English learning.